Implementasi Kebijakan Pemerintah Bagi Pekerja Migran Indonesia (PMI) di Provinsi Jawa Timur Tahun 2021 - Riana Puspa Dewi Santoso; Singgih Manggalou (IAI Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the implementation of government policies for Indonesian Migrant Workers in reducing employment problems in East Java Province in 2021 using the George C. Edwards III approach. The method applied in this research is a descriptive qualitative research method. Data was obtained through interviews, observation and documentation. The data sources used are primary data and secondary data. The research results reveal that the Indonesian Migrant Workers program has been successfully implemented in East Java Province with increased action in handling complaints from Indonesian Migrant Workers